Histone modulation by nuclear localized meningococcal autotransporters - Dutta, Shoma (2020)
The meningococcal autotransporters Adhesion and penetration protein (App) and Meningococcal serine protease A (MspA) are secreted S6-peptidase family autotransporters which have previously been demonstrated to have various roles in meningococcal virulence including functioning as adhesins. One study from our group showed previously that FITC-labelled recombinant App or MspA passenger domain could be taken up by dendritic cells (DCs) and localised to the nucleus; App and MspA can also bind to, and cleave, recombinant histone H3. It was hypothesized the nuclear localisation of App and MspA occurred via nuclear-localisation sequences (NLS) present within them. This study aimed to shed more light on the nuclear localization of these autotransporters, and to identify the NLS of App and MspA.